(untitled) (Journal of Agriculture & Rural Development, 2010)
Orifice meter is a very common flow measuring device installed in a pipe line with minimum troubles and expenses. A coefficient of discharge (Cd) is to be used to get actual discharge from theoretical discharge as different head losses occur in the orifice. An experiment was carried out in the Hydraulic Laboratory of Bangladesh Agricultural University (BAU), Mymensingh to see the variation of Cd with beta ratio, β and Reynold’s number, Re. The test was conducted with five orifice plates having beta ratios of 0.30, 0.35, 0.47, 0.59 and 0.71 installed concentrically in a pipe of 8.5 cm diameter, flowing water through it. Differential pressure head was recorded by a differential mercury U-tube manometer to calculate the theoretical discharges from Bernoulli’s energy equation. It was found that Cd had a positive linear relationship with beta ratio where its dependency was stronger on β than Re in case of low flow rate with highest value of coefficient of determination (R2 = 0.8931) for four-fifth valve opening condition. On the other hand, Cd followed a curvilinear (concave) relationship with Re for all beta ratios except 0.47 which showed convex relationship. However, strong relationships with the value of R2 0.944 and 0.9563 were found for greater beta ratios 0.59 and 0.71, respectively. A combined interpretations of experimental data from a bar diagram revealed that orifice meter with beta ratio 0.60 can be used for efficient pipe flow measurement. Key words: Beta ratio; Reynold’s Number; coefficient of orifice meter. DOI: 10.3329/jard.v7i1.4436 J Agric Rural Dev 7(1&2), 151-156, June 2009